Crime and Immigrant Youth. - Waters, Dr. Tony (SAGE Publications, 1999)
Crime and Immigrant Youth is a unique study of migration as a process that sometimes leads to youthful crime beyond the norms of either the home or host culture. Tony Waters uses data from 100 years of United States immigration records to examine immigrant groups such as Laotians, Koreans and Mexicans in the late 20th century, as well as Mexicans and Molkan Russians in the early years of the century. The study reveals the sequential consequences of a high proportion of young males in an immigrant group: patterned misunderstanding between parents and children; deviant subcultures such as gangs.